Analisis Penerapan Akuntansi Pada Usaha Micro Kecil dan Menengah (UMKM) - Widanengsih, Ade; Suantha, Kasan K. (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
The word Manirancan shop shows that it has not used recording according to accounting standards, it is still simple and not structured so that the information obtained is less accurate. The purpose of this study was to determine how accounting is applied to the Kedai kata manirancan, the obstacles faced by the Kedai kata manirancan and the owner's understanding of financial accounting records. The method used in this study used a qualitative method with observation, interviews, documentation and triangulation. The results of this study indicate that the Kedai kata Manirancan Financial Report Recording System is still based on cash in and out, does not record finances according to accounting standards. The conclusion of the study shows that the Kedai kata manirancan is still simple and does not fully refer to the SAK EMKM financial accounting standards.